The use of Ethnic Terms in the Social Sciences Literature of Peru - Van del Berghe, Pierre L. (1973)
A study of the literature of Social Sciences of Peru reveals the use of a good number of ethnic terms that refer to various groups that make up the heterogeneous population of Peru. A closer examination of the use of these terms by social scientists (both Peruvian and foreign) shows little agreement on their meaning. Such a situation is general and not an exception in social science: One can think of the varied uses of some terms such as "class", "race" or "caste", in American sociological literature. However, we should not leave it aside without having given due importance to some questions that this terminological jungle raises.